Exergoeconomic analysis and optimization of a solar-assisted heating system for residential buildings - Ucar, A.; Inalli, M. (Pergamon-Elsevier Science Ltd, 2006)
In this study, an exergoeconomic model was developed for analysis and optimization of solar heating systems with residential buildings. The optimum collector area (A(c)) and storage volume (V) for solar-assisted heating system in the Elazig, Turkey (38.7 degrees N), weather conditions were obtained using MATLAB optimization toolbox. The energy and exergy losses in each of the components of a solar heating system with seasonal storage were also determined. The results showed that the exergy loss and total cost increased with increasing per house collector area for the trapeze and cylindirical tanks. It was found that the total cost of the cylindrical tank system was higher than that of the other trapeze tank system. The exergy loss at the cylindrical tank was 19.8%, while the exergy loss at the trapeze tank was 8.3%. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: exergoeconomic; optimization; solar energy; building